Sociodemographic Characteristics, Behavioral Problems, Parental Concerns and Children’s Strengths Reported by Parents - Emerich, Deisy Ribas; Carreiro, Luiz Renato Rodrigues; Justo, Ana Maria; Guedes, Paula; Teixeira, Maria Cristina Triguero Veloz (Paidéia (Ribeirão Preto), 2017)
Parental report is essential to understand adaptive difficulties in childhood. The aim of the study was to identify concerns of parents and qualities of children reported by parents, as well as the association of these variables with sociodemographic factors and child behavior problems. Parents of 353 schoolchildren from three public schools and one private school took part in the study. Assessment of behavior problems and parental reports about concerns and children’s strengths were obtained from the Child Behavior Checklist - CBCL. We submitted parents’ answers to the open-ended questions in the CBCL to a lexical analysis with the IRAMUTEQ software. Results concerning ‘strengths’ were related to affective and social interaction, while ‘concerns’ were related to academic performance and prevention of behavior problems. We concluded that parent concerns are targets of preventive interventions in childhood, while child strengths reported by parents are skills that need to be developed, as they help in adaptive functioning.